Legal Politics In Indonesia - Wiranto, Muhammad Jodi; Sudiro, Amad (Journal Of Social Science (JoSS), 2024)
Legal politics in Indonesia has an important role in determining the direction of the formation and implementation of regulations. Article 18 paragraph 4 of the 1945 Constitution of the Republic of Indonesia confirms that regional heads are elected democratically, reflecting the principles of popular sovereignty in the regional government system. This research aims to analyze the dynamics of legal politics related to regional head elections, identify the challenges faced, and provide recommendations for the necessary legal political reforms. The research method used is a qualitative approach with a literature study, which includes an analysis of various legal sources, previous research, and political theories related to local democracy. The results show that although democratic local elections have been implemented, there are various challenges that hinder the effectiveness and integrity of the process. Issues such as the high cost of politics, the practice of money politics, and horizontal conflicts in the community are significant obstacles. In addition, the relationship between politics and law is often intertwined, creating uncertainty in electoral policy. In conclusion, to strengthen a transparent and accountable local government system, comprehensive reforms in local election regulations, increased monitoring of political funding, and public political education are needed. With these steps, it is expected that regional autonomy can run more effectively and in accordance with constitutional values.